KALIMAT INTEROGATIF DALAM SATRIYA-SATRIYA PINANDHITA KARYA KI SURATNO - Dewi Karlina; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to describe the formation of interrogative sentences in the Knight-warrior lil'maldhita works Ki Suratno. This study used a descriptive method with documentation. The results showed that the formation of interrogative sentences contained in Knight-warrior lil'maldhita works Ki Suratno five, namely (1) the formation of interrogative sentences requesting recognition answer "yo / friend (yes)" or "does / does not (not)", or "yo / friend (yes)" or "does not (not)", (2) interrogative sentences which seek answers about one of the sentences formed with the help wondering what the word. Who, where, how, when and why (what, who, where, how and when) according to which part of the sentence in question, (3) interrogative sentences are the answer, ask 'why' was formed with the help wondering why the word or why (why or why), (4) interrogative sentences which seek answers in the form of opinions (about being asked) was formed with the help of words wondering how, how, or how (and how), and (5) of interrogative sentences that justifies, in truth expecting answers to strengthen asked. Interrogative sentences contained in the Knight-warrior lil'maldhita of one hundred and twenty-seven data, among others, (1) Liripun how ?: (2) the truth of how Yayi ?: (3) What ?: tetimbanganmu respectively (4) That the Father? and (5) Then his yayi king ?.Key Words: Interrogative Sentences, Knight-warrior lil'maldhita